Some actual questions of the legal position of board-level employee representatives - Franca, Valentina (Anali PAZU HD, 2022)
The paper focuses on the legal position of board-level employee representatives and raises some actual questions in this regard. The trends on the labour market are presented as well as their potential impact on the implementation of employee participation including board-level employee representatives. According to the analysis of national legislation, researches and other secundary data, there are significant legal possibilities to contribute to a greater legitimacy of board-level employee representatives. Anyhow a revised legislation is needed in order to achieve a greater efficieny of board-level employee representatives since the existing law is outdated.